2012
DOI: 10.1016/j.jhep.2012.01.029
|View full text |Cite
|
Sign up to set email alerts
|

STAT proteins – Key regulators of anti-viral responses, inflammation, and tumorigenesis in the liver

Abstract: Since its discovery in the early 1990s, the Janus kinase (JAK)-signal transducer and activator of transcription (STAT) signaling pathway has been found to play key roles in regulating many key cellular processes such as survival, proliferation, and differentiation. There are seven known mammalian STAT family members: STAT1, 2, 3, 4, 5a, 5b, and 6. In the liver, activation of these STAT proteins is critical for anti-viral defense against hepatitis viral infection and for controlling injury, repair, inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
125
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 153 publications
(129 citation statements)
references
References 134 publications
4
125
0
Order By: Relevance
“…Furthermore, SHP-1 phosphatase-directed therapy (e.g., SC-1) might be a previously unidentified strategy for the discovery of antifibrotic drugs. STAT3 activation has been detected in several human liver diseases, and STAT3 signaling is involved in liver injury, steatosis, inflammation, regeneration, fibrosis, and hepatocarcinogenesis (8,9). The role of STAT3 in liver inflammation and fibrosis is cell type-specific and model-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SHP-1 phosphatase-directed therapy (e.g., SC-1) might be a previously unidentified strategy for the discovery of antifibrotic drugs. STAT3 activation has been detected in several human liver diseases, and STAT3 signaling is involved in liver injury, steatosis, inflammation, regeneration, fibrosis, and hepatocarcinogenesis (8,9). The role of STAT3 in liver inflammation and fibrosis is cell type-specific and model-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms of the antifibrogenic effects remain unclear. The signal transducer and activator of transcription 3 (STAT3) is a transcription factor associated with liver injury, inflammation, and regeneration (8,9). Several studies have shown that interleukin-6 (IL-6) activates STAT3 in HSCs and promotes their survival, proliferation, and activation, thus contributing to liver fibrogenesis (8,10).…”
mentioning
confidence: 99%
“…STAT proteins act as a key signaling cascade mediating cytokine receptor-derived signals, and activation of STAT members serves to transduce signals through the cytoplasm and to function as transcription factors in the nucleus (Miklossy et al, 2013). Among the six distinct STAT members (ie, STAT1, STAT2, STAT3, STAT4, STAT5, and STAT6) (Yu et al, 2009), STAT3 is thought to be a mediator of inflammation (Levy and Lee, 2002), as both IL-6 and TNF have been shown to activate STAT3; IL-6 mediates its effects through the STAT3 pathway; and STAT3 competes with the transcription factor NF-κB (Gao et al, 2012). STAT1 is linked to interferon (IFN) signaling, and STAT5 is linked to IL-2 (Shuai and Liu, 2003).…”
Section: Experimental Sleep Deprivation and Cellular Dynamics And Tramentioning
confidence: 99%
“…STAT1 has previously been considered to function as a tumor suppressor to induce cell-cycle arrest and apoptosis in various types of cancers (30,31). To determine how STAT1 contributes to cell growth and survival in SPEC, various in vitro functional assays were performed using SPAC-1L cells following manipulation of STAT1 activity.…”
Section: Stat1 Functions As a Tumor Prosurvival And Proprogression Gementioning
confidence: 99%